Moderation Analysis of Company Size and Capital Structure on the Influence of Liquidity, Corporate Governance, and Business Risk on Financial Performance - Taristy, Dyana Novita; Asandimitra, Nadia; Hartono, Ulil (Technium Social Sciences Journal, 2023)
Financial performance is an important aspect to consider as it reflects the company's condition and the effectiveness of fund utilization towards the set targets, serving as an evaluation tool and facilitating the company in analyzing and considering factors that can influence any changes, especially in facing the massive economic changes caused by the Covid-19 pandemic. This study aims to analyze the influence of liquidity, corporate governance with institutional ownership mechanism, managerial ownership and audit committee, as well as business risk on financial performance, moderated by company size and capital structure in manufacturing sector companies listed on the Indonesia Stock Exchange (BEI) during the 2020-2021 period. The sample was determined using purposive sampling method, and a total of 168 samples were obtained during the research period. The data analysis methods used were multiple linear regression and Moderate Regression Analysis (MRA). The results indicate that liquidity has a positive influence on financial performance, institutional ownership and managerial ownership do not have a significant influence on financial performance, the audit committee has a negative influence on financial performance, business risk has a positive influence on financial performance, and company size and capital structure cannot directly moderate the occurring influences